Comparison between the efficacy of underwater treadmill and over-ground treadmill training program on knee joint during gait cycle of stroke patients - Zeinab M Abdelrehim; Nahed A Salem; Hossam M El khatib; Mahmoud Y Elzanaty (Annals of Musculoskeletal Medicine - Peertechz Publications, 2021)
Introduction: Gait disorder is a common clinical problem for stroke survivors that impacts performance of activities of daily living.  Objective: This study was conducted to compare between the efficacy of underwater Treadmill Training Program (TTP) and over-ground (TTP) in improving knee joint Range of Motion (ROM) during the gait cycle of stroke patients.  Study design: Randomized control trial.  Methods: Forty male patients suffering from post-stroke gait deficits were assigned randomly into two equal groups: study group (A): Received underwater treadmill training program. Control group (B) received over-ground treadmill training program. Patients of both groups were assessed for knee Range of Motion (ROM) during gait cycle using slow motion video and goniometer iPad application. Assessment was done before and after four weeks of treatment for both groups.  Results: The comparison between groups post treatment showed a significant increase in knee flexion ROM in initial contact and pre-swing phase and increase in knee extension ROM in mid stance phase of the study group (A) compared with that of control group (B).  Conclusion: Under water TTP is more effective than over-ground TTP on improving knee joint ROM during the gait cycle of stroke patients.